Design of power distribution network for microgrid operation - Wang, Fengxia (2017)
Microgrids are small, advanced electric grid with features that make them especially adept at managing energy and ensuring its reliable delivery. With independent control system, it can provide the power and heat to local consumers efficiently. Nowadays, microgrid can be found in university campuses, hospital, military bases, airports and some large industrial facilities. Within microgrid there are one or more kinds of traditional energy sources, such as solar, wind and fuel cell, etc. All these sources are called renewable energy sources. In this report, a microgrid system is proposed to ensure that the microgrid can operate under: (i) grid-connected mode and working in a dependable and efficiently way; (ii) provide an uninterrupted reliable flow of power as the microgrid is working in islanded mode.